Inter- and Intraobserver variability of attenuation coefficient measurement in innovative ultrasound diagnosis of metabolic dysfunction-associated steatotic liver disease: a cross-sectional study - Zhaivoronok, Maksym; Dynnyk, Oleh; Livkutnyk, Olexandr; Yerokhovych, Viktoriia; Yuzvenko, Violetta; Serednia, Iryna; Melnychenko, Yelizaveta; Kobyliak, Nazarii (Frontiers in Medicine, 2025)
IntroductionEvaluation of the ultrasound attenuation coefficient is widely used in the diagnosis of steatotic liver disease (SLD). US steatometry with real-time attenuation coefficient measurement (ACM) is an imaging tool that can replace and surpass the B-mode and improve the noninvasive diagnosis of SLD.AimTo evaluate the intra- and interobserver variability of ACM for the assessment of SLD.Materials and methodsA single-center cross-sectional study was conducted at the Kyiv City Clinical Endocrinology Center. We examined 52 patients (25 men and 27 women) with a mean age of 53.2 ± 4.73 years. B-mode and ACM were performed on a Soneus P7 US system (Ultrasign, Ukraine). Examinations were performed by 2 radiologists with 28 (expert 1) and 17 (expert 2) years of experience and 4 general practitioners (GPs) without US experience (nonexperts 1–4). The training of 4 GPs on mastering the ACM was only 60 min due to US steatophantom. Each doctor performed 5 measurements of the ACM for each patient. The inter- and intraobserver variability of the results was determined by using an intraclass correlation coefficient (ICC) with a 95% confidence interval (95% CI).ResultsThe overall intraobserver variability after 5 days of examination was as follows: for expert 1–0.958 (95% CI 0.938–0.974); for expert 2–0.936 (95% CI 0.905–0.980); nonexpert 1–0.891 (95% CI 0.843–0.929); nonexpert 2–0.915 (95% CI 0.876–0.945); nonexpert 3–0.927 (95% CI 0.893–0.953); nonexpert 4–0.880 (95% CI 0.827–0.927). Interobserver variability at the final timepoint (day 5) was as follows: between experts 1 and 2, 0.942 (95% CI 0.898–0.967); between nonexperts 1–4 overall, 0.871 (95% CI 0.800–0.921); and overall, 0.922 (95% CI 0.883–0.951).ConclusionReal-time US steatometry with ACM measurement is an informative, simple method with excellent intra- and interobserver variability and a reproducible method for population assessment for the early diagnosis and staging of SLD. The simplicity of ACM technology allows general practitioners to master the technique within 60 min. ACM measurements can be effectively employed by general practitioners (GPs) for population screening, enabling timely identification and management of MASLD.